Penerapan Asas Keadilan Dalam Hal Penjatuhan Sanksi Pidana Bagi Pelanggar Pembatasan Sosial Berskala Besar Di Masa Pandemi - Anita Dwi Lestari; Vidi Al Imami; Mutia Aldina Arafah; Irya Rizka Zahida; Ari Ramadhan; Evi Oktarina (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2022)
The increasing rate of spread of the COVID-19 virus has prompted the government to reiterate its policy of restricting public activity. The increased rate of transmission of Covid-19 virus is estimated to be due to the new variant of SARS-CoV-2 (Delta) and increased mobility of citizens during holidays. The government must issue new rules and policies in this situation, which is crucial in the current abnormal state conditions. Hopefully these new laws and policies will help maintain order and peace. Normative legal research, or legal research that uses library material or secondary data, is used. If viewed from the perspective of justice in society, the granting or enforcement of criminal sanctions has not given a sense of justice to the society if the perpetrator.